Omega-3 Polyunsaturated Fatty Acids Supplementation Alleviate Anxiety Rather Than Depressive Symptoms Among First-Diagnosed, Drug-Naïve Major Depressive Disorder Patients: A Randomized Clinical Trial - Yang, Rong; Wang, Lu; Jin, Kun; Cao, Song; Wu, Chujun; Guo, Jimin; Chen, Jindong; Tang, Hui; Tang, Mimi (Frontiers in Nutrition, 2022)
Background: Omega-3 polyunsaturated fatty acids (n-3 PUFAs) augmentation of antidepressants have shown greater potential on the prevention and treatment of major depressive disorders (MDD). Method: A total of 72 outpatients with first-diagnosed depression were recruited. The daily dose of 2.4g/day n-3 PUFAs or placebo plus venlafaxine were used for over 12 weeks. The outcomes were assessed by Hamilton depression scale (HAMD), Hamilton anxiety scale (HAMA), Beck depression inventory (BDI), Self-rating anxiety scale (SAS), the rate of responders and the rate of full remission. Results: Both groups exhibited improvement on clinical characteristics at week 4 and week 12 compared with baseline. The rate of responders for anxiety at week 4 in n-3 PUFAs group was significantly higher than that in placebo group (X2 = 4.182, p = 0.041). Pearson correlation showed that Childhood Trauma Questionnaire (CTQ) had positive correlation with HAMA (r = 0.301, p = 0.012), SAS (r = 0.246, p = 0.015), HAMD (r = 0.252, p = 0.038) and BDI (r = 0.233, p = 0.022), and negative correlation with EPA level (r = -0.238, p = 0.029). Social Support Rating Scale (SSRS) had negative correlation with SAS (r = -0.244, p = 0.015) and BDI (r = -0.365, p = 0.000). The AUC of combined CTQ and SSRS receiver operating curve (ROC) for placebo group to evaluate the responders of depressive or anxiety symptoms was 0.783 ± 0.092 (95%CI: 0.602-0.965) and 0.728 ± 0.098 (95%CI: 0.535-0.920) respectively at week 12. Conclusions: This trial found that n-3 PUFAs supplementation in favor of venlafaxine alleviated the anxiety symptoms rather than depressive symptoms at the early stage of treatment (4 weeks) for first-diagnosed, drug-naïve depressed patients. However, the advantage disappeared in long-term treatment. Furthermore, childhood abuse and social support are closely related to the clinical and biological characteristics of depression. Both childhood trauma and lack of social support might be predictors of poor prognosis in depression. Trial registration: clinicaltrials.gov identifier—NCT03295708.